Analisis Implementasi Manajemen Risiko Pada Pendistribusian Zakat di LAZISMU Banyumas - Rahma Kamila; Hastin Tri Utami (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
As modern times develop, the distribution of zakat has undergone many changes. Distribution through correct procedures is expected to meet the needs of mustahik and reduce unwanted risks, thereby helping to improve the welfare of mustahik. The application of risk management in zakat distribution functions to detect risks that occur so that solutions can be created to minimize existing risks. The aim of this research is to find out the procedures for distributing zakat and knowing the risk management of distributing zakat funds at LAZISMU Banyumas using qualitative data collection techniques, namely interviews, observation and documentation. Primary data was generated through interviews with directors and distribution managers and related mustahik. Observations were carried out by visiting LAZISMU Banyumas directly to observe procedures and risk management for the distribution of zakat funds at LAZISMU Banyumas carrying out the distribution stages in an orderly manner in accordance with structured steps for asnaf whose criteria have been determined with various distribution patterns. The implementation of risk management at the Amil Zakat Muhammadiyyah Banyumas Institution found risks classified according to levels in the form of high risk, medium risk and low risk.